The Influence of Competence and Motivation on ASN Performance moderated by the Work Environment at the Makassar City Regional Financial and Asset Management Agency. - Tahir, Muh.; Abd. Samad, Hasniaty, (YUME : Journal of Management, 2024)
The purpose of this study is to determine and analyze the influence of competence and motivation on the work environment and performance at the Makassar City Regional Asset Management Agency.This study took a sample of 70 employees at the Makassar City Regional Asset Management Agency. The results of this study found that Competence did not have a significant effect on ASN performance at the Makassar City BPKAD office. Motivation had a positive and significant effect on ASN performance at the Makassar City BPKAD office. The work environment does not have a significant effect on ASN performance at the Makassar City BPKAD office. The role of the work environment is not significant in moderating the relationship between competence and ASN performance at the Makassar City BPKAD office. The role of the work environment is not significant in moderating the relationship between motivation and ASN performance at the Makassar City BPKAD office.Keywords: Competence, Motivation, Work Environment and Performance